Surface ozone variations at the great wall station, Antarctica during austrial summer - Franky Herman (2020)
Surface Ozone (O3) is a secondary pollutant which toxic to human health, and a greenhouse gas which is one of the prime climate forcers. Due to the clean atmospheric environment of the Antarctic region and given the complexity of O3 chemistry, the observation of surface O3 variability in this region is necessary in the quest to better understand the potential sources and sink of polar surface O3. This study highlights the observation on surface O3 variability at the Great Wall Station (GWS) during austral summer in December 2018 and January 2019. The continuous in-situ surface O3 measurement at the GWS, Antarctica was carried out using the EcoTech Ozone analyzer while meteorological data was obtained from the conventional auto-observational station operated at the GWS. To have a better understanding of surface O3 latitudinal distribution, the spatial and temporal of surface O3 data obtained online from the World Meteorology Organization of World Data Centre for greenhouse gases (WMO WDCGG) were then compared to give an indications of its spatial and temporal characteristic. The HYSPLIT model (Hybrid Single-Particle Lagrangian back-trajectory) was employed to have a better picture on the overall impact of air mass transport toward the surface O3 formation over the region. Lastly, to have a better discernment on the potential impact of meteorology to the surface O3 formation, statistical principal analysis (PCA) was employed to give a confidence measure over which meteorological parameter play more pivotal role on affecting surface O3 background level. The results show that despite being characterised as stable surface O3 concentration with standard deviation value of 0.24 ppbv throughout the entire period of observation, though the hourly summer surface O3 distribution at GWS varies from 4.45 ppbv to 7.81 ppbv. The online dataset from WDCGG showed that the summer characteristic of surface O3 at GWS are oneto- three times lower than what been observed at other research station. The unique characteristic of surface O3 of GWS can temporarily emphasized by its synoptic marine air mass characteristic with coefficient correlation value of 0.17, significant at value of 0.1. The statistical result of PCA shows that three principal components factors with eigenvalues cut-off unity value of 70%, and only atmospheric pressure as well surface temperature in factor 1 shows significant positive correlation with surface O3 with coefficient value of 0.667 and 0.563, respectively. While wind speed and wind direction in factor 3 which significant at 0.701 and 0.748 respectively, have more pivotal role to cause residual change in diurnal surface O3 concentration. To put something into perspective, the surface O3 variability at the GWS suggesting that the marine air mass could be important source of low surface O3 level, and the temporal characteristic controlled by combined local photochemical process and air mass transport subjected to the availability of its precursor, or halogen species and its weather condition.